An Effective Bedside Lavage Technique for Management of Septic Arthritis of the Ankle - Steven DeFroda; Andrew Gil; Joe Harris; Siddhartha Sharma; Soheil Ashkani-Esfahani; Gregory R Waryasz (Journal of Foot and Ankle Surgery (Asia Pacific))
Septic arthritis of the ankle can result in short- and long-term disabilities and fatal complications if not addressed promptly. Urgent arthroscopic or open joint lavage is the standard of care in cases with septic arthritis. However, this may be delayed in older patients with comorbidities and immunocompromised individuals, for achieving preoperative optimization. To counter such situations, we present a simple and effective bedside joint lavage technique that relies on continuous irrigation and suction and can therefore prevent unwarranted delays in the operative management of these cases.